The influence of the audio and video, as a teaching tool, in the in-class reinforcement of the listening comprehension skill to generate oral participation of Instituto Técnico EXSAL senior high school students taking bachillerato general con diplomado opcional en idioma inglés - Guardado Salguero, Eliseo
In the last decades the implementation of multimedia sources in teaching process has allowed teachers to go in the mind of the students in classroom as a result of providing that help to enhance listening comprehension skills and the oral participation. According to Meskill (1996), the last decades have brought to language teaching and learning a wide range of [multimedia] technologies. Besides, Shrosbree (2011) mentions that there is an obvious appeal to using video in the language classroom. Nevertheless, students face serious problems as lack of motivation or unfamiliarity with unknown sounds on that target language (English), which eventually can make them feel disappointed. In fact, they do not get either full participation on in-class listening activities or good grades in listening assessment tests. However, when teachers of English teach listening with audio, as it has been taught for so long time ago, students recognize that the combination of both audio and video is better. Instead of the rather unnatural task of listening to a disembodied voice emanating from an audio player, learners are able to see the speaker and elements of the surrounding environment.